Anticoagulant prescribing in patients with ischaemic stroke: what has changed over a decade?. Issue 10 (27th October 2020) - Sharobeam, Angelos; Jones, Brett; Watters, Aidan; Das, Chandi; Lueck, Christian
Abstract: A study at our institution conducted 10 years ago identified that warfarin was under‐utilised in patients with atrial fibrillation. We replicated this study and compared the results. There was a significant increase in the proportion of patients appropriately anticoagulated (63% vs 9%, P < 0.001). Eighty‐seven percent of eligible patients were appropriately anticoagulated on discharge (86% previously). Seventy‐two percent of treated patients were prescribed a direct oral anticoagulant. Of these, 10% were discharged with a sub‐therapeutic dose without obvious explanation.